[…] Ja nie wykładam tutaj estetyki. Wincenty Pol a sztuki plastyczne - Zaremba, Magdalena (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
Taking into consideration, as it is called by Sudolski, a controversial reception of the works of the author of Pieśń o ziemi naszej (Song of Our Land)43, it seems worthwhile to systematise attitudes visible in reference books and to determine Pol’s place among 19th century literary critics. Basing on reference books and 19th century art criticism, one may notice a discrepancy between the vision of the poet as a pioneer of art and a master of literary romantic landscape and as a poet who, with his descriptions, fits not only in the then artistic thought but also he is an unoriginal, “goodhearted”, sentimental author. A most relevant step is to introduce an axis which would present the cohesion of artistic programme not only in Pol’s essays or correspondence but also in chosen poetic works. The remarks on the role of art in Pol’s works are scarce; yet, they fit in the programme of the national reception of the then art and the vision of its post-partition shape. It is completed with fragments of poetry or literary fractions of “krajowidoki” (landsights). The context is formed by words addressed to painters: Juliusz Kossak, January Suchodolski or Wojciech Korneli Stattler being rather a testimony of familiarity of some kind than discourses about painting similar to those written by Juliusz Słowacki in the forties of the 19th century.